A phase-II study of atezolizumab in combination with obinutuzumab or rituximab for relapsed or refractory mantle cell or marginal zone lymphoma or Waldenström's macroglobulinemia. Issue 5 (16th April 2022) - Panayiotidis, Panayiotis; Tumyan, Gayane; Thieblemont, Catherine; Ptushkin, Vadim V.; Marin-Niebla, Ana; García-Sanz, Ramon; Le Gouill, Steven; Stathis, Anastasios; Bottos, Alessia; Hamidi, Habib; Katz, Pablo; Perretti, Thomas; et al.
Abstract: We report efficacy, safety and biomarker data from a phase-II study evaluating atezolizumab (eight 21-day cycle as induction therapy) in combination with obinutuzumab in patients with relapsed/refractory mantle cell lymphoma (MCL, n  = 30) or Waldenström's macroglobulinemia (WM, n  = 4), and in combination with rituximab in patients with marginal zone lymphoma (MZL, n  = 21). All patients received atezolizumab monotherapy as maintenance for ≤10 cycles. Objective response rates at end of induction were 16.7% (MCL) and 42.9% (MZL), with no responses in WM. Median duration of response was 6.8 months (range 5.7–not estimable) for MCL and not reached for MZL. Treatment-emergent adverse events (TEAEs) occurred in 93.3%, 95.2% and 100% of MCL, MZL and WM patients, respectively. One fatal TEAE (pneumonia) occurred in each of the MCL and MZL groups. Biomarker analysis highlighted the importance of characterizing the immune environment to optimize efficacy of immunotherapy regimens. Trial registration details: EudraCT: 2016-003579-22